Fetal renal artery (RA) volume blood flow is altered in early-onset intra-uterine growth restriction (IUGR) and has a non-linear relationship with AFI. (18th April 2012) - Mullins, E; Story, L; Prior, T; Kumar, S
Abstract : Introduction: IUGR is associated with oligohydramnios. We investigated fetal RA parameters in normal and IUGR pregnancies and their correlation with amniotic fluid index (AFI). Method: Women booking at Queen Charlotte's & Chelsea Hospital were recruited. Serial scans for growth, vessel diameter (VD) and power Doppler of the RA were performed at 24, 28, 32 and 36 weeks or as indicated. Volume blood-flow (VBF) was calculated. Parameters were adjusted for estimated fetal weight (EFW). IUGR severity was stratified by umbilical artery, middle cerebral artery and venous Doppler changes. Statistics with SPSS.v.19. Results: 248 women (112 IUGR, 136 normal controls) were recruited. 848 scans were performed. RA VD and VBF increased with gestation. RA VD and VD/kg were greater in IUGR between 24-32 weeks (p=0.04, p=0.01 respectively). This correlated with IUGR severity at 24 weeks (p=0.03) and 28 weeks (p=0.01). RA VBF and VBF/kg were increased in IUGR from 24-32 weeks (p=0.04, p<0.001 respectively). This was significantly associated with the severity of IUGR at 32 weeks (p=0.027), approaching significance at 24 weeks. AFI correlated positively with EFW (p=0.001) and negatively with severity of IUGR at 24-32 weeks (p<0.01) and RA VBF and VBF/kg (after adjustment for gestation, in normal and IUGR pregnancies, p<0.001). Discussion: Fetal RA- VD and VBF were correlated with IUGR severity in early-onset IUGR. In normal pregnancies, AFI peaked in mid-gestation and declined towards term. There was non-linear relationship between RA VBF and AFI in normal and IUGR pregnancies, illustrating altered renal function in the maturing fetal kidney.